2024
DOI: 10.3389/fpubh.2024.1323102
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pharmacist-led collaborative care on clinical outcomes in type 2 diabetes mellitus: a multicenter randomized control trial

Muhammad Zahid Iqbal,
Saad Saeed Alqahtani,
Naeem Mubarak
et al.

Abstract: BackgroundHealth care providers are mandated to deliver specialized care for the treatment and control of type 2 diabetes mellitus. In Malaysia, Diabetes Medication Therapy Adherence Clinics (DMTAC) in tertiary hospitals have designated pharmacists to administer these services.ObjectiveTo assess the effects of pharmacist-led interventions within DMTAC on the outcomes of patients with type 2 diabetes mellitus in two distinct hospitals in Kedah, Malaysia.MethodsPatients with type 2 diabetes were randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…By taking medication on time as prescribed, the infection can be better controlled. These findings align with a study conducted by Iqbal et al, (2024) in Malaysia, which found that patients who were more compliant with their treatment had better outcomes in a randomized control trial evaluating patients with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 88%
“…By taking medication on time as prescribed, the infection can be better controlled. These findings align with a study conducted by Iqbal et al, (2024) in Malaysia, which found that patients who were more compliant with their treatment had better outcomes in a randomized control trial evaluating patients with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 88%